Ammonia recovery from ion exchange brine via hollow fibre membrane contactors: operational insights and product formation - Sakar, Hacer; Soares, Ana (Elsevier, 2025)
Ammonia removal from municipal and industrial wastewater streams is critical to ensure environmental protection. Ion exchange (IEX) processes can selectively capture NH4 +-N from wastewater, but this involves a chemical regeneration step with brine (4 % NaOH) that if not suitably managed, can lead to high chemical costs and significant environmental impacts. To achieve efficient brine management, NH4 +-N must be recovered so the regenerant can be reused over and over. This study evaluated the feasibility of hollow fibre membrane contactors (HFMC) for NH4 +-N recovery from IEX brine to enable its reuse. The nitrogen rich brine with 1190 mg NH4 +-N/L, collected from a pilot-scale IEX, was processed in two HFMC modules in series, with sulfuric acid used as the stripping solution. The HFMC operational parameters were investigated and optimised leading to 99.98 % NH4 +-N recovery efficiency. Water transport was influenced by the brine ammonia concentration: at 2000 mg NH₄+-N/L, 20 % water moved to the stripping side, whereas at 200 mg NH₄+-N/L, a 12 % decrease in stripping solution volume occurred. The highest mass transfer coefficient was 6.1 1/h with synthetic brine, increasing to 9.38 1/h with real wastewater brine, indicating enhanced efficiency with wastewater-derived solutions. The recovered ammonium sulphate salt closely matched standard composition and was free from organics, pathogens, and most inorganics and metals, making it suitable for various industrial applications. Overall, this two-step process concentrated NH₄+-N from 42 mg/L in secondary wastewater to 32 g NH₄+-N/L in under 10 h. The findings demonstrate HFMC feasibility for ammonia recovery from municipal wastewater, offering a sustainable, efficient, and economic solution without sludge production or greenhouse gas emissions, supporting net-zero targets and a zero liquid discharge strategy.
Keywords: 40 Engineering; 13 Climate Action; 4004 Chemical engineering; 4011 Environmental engineering; 4016 Materials engineering; Membrane contactors; Ion exchange brine; Ammonia recovery